Characterization of Eco-Friendly Cutting Fluid Developed from Neem Seed Oil (Nigerian Journal of Technology, 2022)
Cutting fluid is a key component in retaining workpiece quality, tool life and overall high productivity in machine operations. It is needed as input for minimal surface roughness, minimal tool wear and better machining finished product. This study addressed tool wear and surface roughness by evaluating optimal factor effectiveness of the surface roughness and tool wear during turning of AISI 304 alloy steel using an environmentally friendly fluid. The non-biodegradable and non-recyclable nature of conventional cutting fluids as mineral oils have raised serious concerns with the research community and prompted the renewal of research in this area with focus on replacing the mineral based cutting fluids with environmentally friendly cutting fluids such as neem seed prepared cutting fluid (N-PCF). The neem seed oil (NSO) was sourced locally and characterized by investigating the physiochemical properties as well as it’s fatty acid composition (FAC). The cutting fluid formulation was 1:9 of oil to water in the ratio. The cutting fluids which aided surface roughness and tool wear reduction during turning of the austenitic stainless steel AISI 304 and improved the carbide insert tool was evaluated and compared with mineral oil-based cutting fluid. Also, the response surface method (RSM) of experimental design and Grey relational analysis (GRA) multi-response optimization were employed respectively. The experimental results revealed that the formulated oil showed 8.67 pH value, 0.50 mm2/s viscosity, resistant to corrosion, stable and deep yellowish colouration. The multi-response optimal factor combination obtained from GRA showed multi-response effect of the formulated Neem seed prepared cutting fluid at feed rate of 0.82 mm/rev, depth of cut of 0.65 mm and cutting velocity of 800 rev/min while that of Mineral prepared cutting fluid (M-PCF) was achieved with feed rate (0.82 mm/rev), depth of cut (0.65 mm) and cutting velocity (500 rev/min). GRA and RSM results showed acceptable parameters that contribute to the science of machining and this is in good agreement when compared with those obtained from other cutting fluids used for turning operation.